2019
DOI: 10.2147/copd.s228465
|View full text |Cite
|
Sign up to set email alerts
|

<p>Physical Activity in Patients with Chronic Obstructive Pulmonary Disease on Long-Term Oxygen Therapy: A Cross-Sectional Study</p>

Abstract: Background and aimThere are few studies evaluating physical activity (PA) in patients with chronic obstructive pulmonary disease (COPD) on long-term oxygen therapy (LTOT).AimTo assess PA in hypoxemic COPD patients on LTOT.MethodsIn this cross-sectional study, we compared lung function, arterial blood gases, respiratory and peripheral muscle strength, 6-min walking distance (6MWD), daily energy expenditure and steps, and health-related quality of life (HRQL) in COPD patients on LTOT (LTOT group) versus two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
(60 reference statements)
2
4
0
1
Order By: Relevance
“…We used accelerometry to provide an objective assessment of physical activity in this population and found that COPD patients with chronic respiratory failure have a remarkably low level of domestic daily life activities. 41 We also confirmed the existing relationship between physical frailty and low daily physical activity previously reported in healthy older adults. 42 Regardless of the physical frailty status, the number of steps per day and the time spent in moderate physical activity were well below the guideline recommendations.…”
Section: Discussionsupporting
confidence: 90%
“…We used accelerometry to provide an objective assessment of physical activity in this population and found that COPD patients with chronic respiratory failure have a remarkably low level of domestic daily life activities. 41 We also confirmed the existing relationship between physical frailty and low daily physical activity previously reported in healthy older adults. 42 Regardless of the physical frailty status, the number of steps per day and the time spent in moderate physical activity were well below the guideline recommendations.…”
Section: Discussionsupporting
confidence: 90%
“…Exercise tolerance, daily physical activity, healthrelated quality of life, and survival are reduced in COPD patients with chronic respiratory failure compared to early stages of the disease. 11,22,37,38 The 6MST is an attractive field test to evaluate exercise tolerance outside of a hospital. 30 Six (31.6%) of the initially frail participants were unable to perform the 6MST and consequently received the score of zero.…”
Section: Impact Of Frailty On Pulmonary Rehabilitation Effectiveness ...mentioning
confidence: 99%
“…Few studies have evaluated the sedentary time of patients on LTOT [9,43], and the sedentary time of Japanese patients on LTOT has not been clarified. The sedentary time of patients on LTOT has been reported to be 623 min [9].…”
Section: Characteristics Of Sedentary Time In Patients On Ltotmentioning
confidence: 99%